SIKAP ANTI KORUPSI DITINJAU DARI BUDAYA MALU DAN NILAI AKADEMIS MAHASISWA - Netty Kesuma; Khairuman Khairuman (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
This research aims to find out: (1) the influence of anti-corruption attitudes reviewed from the culture of shame on college students of Adiguna Maritime Polytechnic of Indonesia Medan, (2) the influence of anti-corruption attitudes reviewed from academic values on the cognitive aspects of Adiguna Maritime Polytechnic Indonesia Medan college students, (3) whether anti-corruption attitudes simultaneously have an influence when reviewed from the culture of shame and academic value on the cognitive aspects of Adiguna Maritime Polytechnic Indonesia Medan college students. The sample was taken using proportional random sampling where the sample was determined from the representatives of each class that participated in the Introductory course of Legal Science selected randomly so that the sample number as many as 42 college students. The instruments used in this study are a culture of shame consisting of 20 question items, an anti-corruption stance consisting of 15 questions and an academic value consisting of 20 question items. The entire instrument is validated using the validity of the contents. The data in this study is quantitative and qualitative data. Data analysis techniques for those used in this study used SPSS with the use of chi square tests, multiple regression tests and Anova tests. The results of the study obtained: (1) anti-corruption attitudes have the influence of reviewed from the culture of shame on college students of Adiguna Maritime Polytechnic of Indonesia Medan, (2) anti-corruption attitudes have an influence reviewed from academic values on the cognitive aspects of Adiguna Maritime Polytechnic Indonesia Medan college students. (3) anti-corruption attitudes simultaneously have an influence when reviewed from the culture of shame and academic value on the cognitive aspects of Adiguna Maritime Polytechnic Indonesia Medan college students.